Álgebras de explosão e birracionalidade - Vasconcelos, Liliane Silva Batista (2022)
This dissertation deals with the relationship between the equations of ideals for the presentation of explosion algebras and the concept of birationality. To achieve this purpose, we make two preliminary chapters introducing the notions that play a central role in the statement of the main results of the work. These results consist of a weak version of a birationality criterion due to Doria-Hassanzadeh-Simis and the application of this criterion ´ to certain ideals of height two in a ring of polynomials in three variables.